Workload and the quality of nursing care in critically ill patients: a systematic review - Esquivel-Franco, C.G. (Revista de Ciencias Médicas Torreón, 2026)
Introduction: The Intensive Care Unit (ICU) is a highly complex environment that requires continuous and specialized care, exposing nursing staff to a high workload. This overload may affect both the physical and mental health of professionals, as well as the quality and safety of care provided to critically ill patients.Objective: To evaluate whether workload overload among nursing staff affects the quality of care for critically ill patients in intensive care units.Methodology: A systematic literature review was conducted following PRISMA guidelines. The search was carried out between March and May 2022 in the PubMed, Google Scholar, SCIELO, LILACS, and ScienceDirect databases. Studies published between 2010 and 2022 in Spanish, English, and Portuguese, related to nursing workload in adult ICUs, were included. After applying inclusion and exclusion criteria, 16 articles were selected for the final analysis. Methodological quality was assessed according to the hierarchy of evidence proposed by Stetler et al.Results: The analyzed studies show a significant association between nursing workload overload and deterioration in the quality of care. A high workload was associated with increased healthcare-associated infections, eficiencia y calidad de las mismas, dado que por cada paciente que sea asignado por una enfermera aumente el riesgo de mortalidad (Isabel et al., 2021; Mol et al., 2017). Por esta razón, el ámbito psicosocial influye de manera positiva como negativa hacia la salud, el bienestar y rendimiento del enfermero(a), en los cuales se presentan como exigencias psicológicas; ajuste entre las tareas y los tiempos laborales, familiares y sociales; control sobre el trabajo; apoyo social e instrumental de compañeros y superiores; calidad de liderazgo; compensaciones del trabajo; y seguridad en el empleo. En cuanto a las demandas mentales son una de las principales fuentes de carga mental, teniendo efectos perjudiciales para la salud de los trabajadores y para el logro de los objetivos de la organización (Ceballos- Vásquez et al., 2015). ventilator-associated pneumonia, pressure injuries, medication errors, and higher mortality. Instruments such as the Nursing Activities Score (NAS) and the Therapeutic Intervention Scoring System (TISS) were the most frequently used to measure workload, demonstrating that higher scores are associated with poorer clinical outcomes and reduced patient safety.Conclusions: The available evidence confirms that excessive nursing workload negatively impacts the quality of care for critically ill patients. Insufficient staffing levels and inadequate personnel distribution in the ICU are key factors contributing to adverse events and increased mortality. Adequate human resource planning and continuous workload monitoring are essential to ensure safe, effective, and high-quality care in the intensive care setting.